Pengaruh Independensi Dan Kompetensi Terhadap Kinerja Auditor di Moderasi Etika Auditor - Abdul Aziz; Siti Maghfiroh (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
Public Accounting Firms provide accounting services such as auditing, financial consulting, and taxation, which are divided into attest services such as auditing financial statements and non-attest services such as management consulting. Auditors have an important role in improving company performance by carrying out tasks according to agreed standards. Auditor performance evaluation is carried out to assess the effectiveness of the tasks that have been completed. The purpose of this study was to determine and analyze the relationship between independence and competence on auditor performance moderated by auditor ethics. This study uses a quantitative approach with 44 respondents from auditors at public accounting firms in Jakarta. SPSS is used as a data analysis technique. The results showed that independence and competence affect auditor performance. This study also examines the moderation relationship with the results showing that independence affects auditor performance moderated by auditor ethics and competence affects auditor performance moderated by auditor ethics.